Design a precision motion control of an upper limb robotic arm - Kwan, Ze Zhen; Mohd Khairuddin, Ismail; Mohd Razman, Mohd Azraai; Anwar, P. P. Abdul Majeed; Mohd Isa, Wan Hasbullah (Penerbit UMP, 2022)
Trajectory tracking is utilized in medical rehabilitation programs at the early stage of rehabilitation in order to track the performance of the patient in performing the prescribed task. The robotic arm has been utilized to accomplish this due to it precision and provide repetitive motion. The goal of this study is to design and simulate a two-degree-of-freedom robotic arm that can effectively track a trajectory. As a result, this study discusses the modelling, simulation, and control of a Two Degree of Freedom (2-DOF) Robot Arm to attain that goal. First, the robot specifications are provided, as well as the forward and inverse kinematics of a 2-DOF robot arm. The dynamics of the 2-DOF robot arm were then defined using the Euler- Lagrange Equation to obtain motion equations. A PID controller was used to construct a control design for the robot's controller. MATLAB is used to record all the data, including the margin of error, overshoot, and peak settling time. The data is identified using the PI and PID controllers, in which the error is smaller than 7 and 1.5, respectively. The controller was then used to create a prototype model by using MATLAB Sim Mechanics. The data obtained indicates that a PID controller is the best fit for this rehabilitation robot.